Portofolio dengan Menggunakan Model Indeks Tunggal dan Metode Z - Werner R. Murhadi (Jurnal Manajemen Maranatha, 2013)
This study aimed to establish the optimal portfolio using a single index model approach and Z methods. This study used a sample of companies included in the LQ-45 period February 2009-January 2013. The results showed that the portfolio returns by using a single index models and Z methods did not give different results.The use of a single index model can provide a smaller risk than the use of Z method. The use of a single index model produces 11 stocks included in the portfolio, while the Z method produces 6 stocks included in the portfolio. The results indicated Z method is more suitable to investors who have limited funds and limited time.